B12 Treatment with arimoclomol does not lead to rescue of motor or striatal deficits in the YAC128 mouse model of Huntington's disease. (16th November 2010) - Pouladi, M A; Carroll, J; dar Santos, R; Bertram, L; Hayden, M R
Abstract : Background: Huntington's Disease (HD) is an inherited neurological disorder characterised by loss of motor coordination, cognitive dysfunction and psychiatric disturbances that remains without a cure. Arimoclomol, a compound reported to enhance cellular stress induced heat shock protein response, has been shown to be neuroprotective in a mouse model of amyotrophic lateral sclerosis (ALS). Aims: To examine whether treatment with arimoclomol would (a) protect against quinolinic acid (QA) mediated excitotoxicity and (b) improve the phenotype of the YAC128 mouse model of HD. Methods: 3 month old wild-type (WT) mice were pretreated with PBS or arimoclomol (40 mg/kg, intraperitoneally followed by an intrastriatal injection of QA (20 nmol) 30 min later). Striatal lesion volume in arimoclomol and PBS treated animals was assessed 7 days later. YAC128 and WT mice were treated with 80 mg/kg of arimoclomol administered in the drinking water for 10 months, starting at 2 months of age. YAC128 and WT animals receiving water only served as no treatment controls. Motor function was assessed using the accelerating and fixed speed rotarod tests at 2, 4, 6, 8, 10 and 12 months of age. Striatal pathology was assessed using unbiased stereology at 12 months of age. Results: In animals that received intrastriatal injections of QA, there was no significant difference in lesion volume between those pretreated with arimoclomol compared with those treated with PBS only. In animals receiving arimoclomol chronically, there was no significant difference between arimoclomol treated and untreated WT animals in motor performance, as assessed by the accelerating and fixed speed rotarod tests. The motor performance of untreated YAC128 HD mice was significantly lower compared with that of untreated WT animals. Treatment with arimoclomol had no effect on motor performance of YAC128 HD animals compared with untreated YAC128 HD animals. Further, brain weight and striatal volume of untreated YAC128 HD animals was significantly lower compared with untreated WT animals. Treatment with arimoclomol had no effect on brain weight or striatal volume of YAC128 HD animals compared with untreated YAC128 HD mice. Conclusions: Our findings demonstrate that treatment with arimoclomol does not lead to improvements in motor function or rescue of striatal pathology in YAC128 HD mice.